Schöpferische Zerstörung - Unternehmen haben die Rezession mit teilweise neuen beschäftigungspolitischen Instrumenten bewältigt. - Schneider, Martin; Rütten, Karl-Georg (Personal)

SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (Proceedings of the International Conference on Information Society (i-Society 2011))

Seeking the VALUE in IS Business Value Research - An Agenda for investigating Synergies Between Socio-organizational Change, IS Capabilities Change, and IS Innovation - Schryen, Guido (IS Capabilities Change, and IS Innovation, Proceedings of the 19th European Conference on Information Systems (ECIS 2011), Helsinki)

Service orientation of manufacturing companies: A necessary or sufficient condition for firm profitability? - Eggert, A; Münkhoff, E; Thiesbrummel, C (Proceedings of the 40th European Marketing Academy (EMAC) Conference)

Service orientation of manufacturing companies: A necessary or sufficient condition for firm profitability? - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (40th EMAC Annual Conference, Ljubljana)

Short- and long-term impact of remarkable economic events on the growth causes of China–Germany trade in agri-food products - Guo, Zhichao; Feng, Yuanhua; Tan, Xiangyong (Economic Modelling)

Simulation Aided, Knowledge Based Routing for AGVs in a Distribution Warehouse - Klaas, Alexander; Laroque, Christoph; Fischer, Matthias; Dangelmaier, Wilhelm (Proceedings of the 2011 Winter Simulation Conference)

Situativ trainierte Regeln zur Ablaufsteuerung in Fertigungssystemen und ihre Integration in Simulationssysteme - Aufenanger, Mark

Slipstream: architecture options for real-time process analytics - Janiesch, Christian; Matzner, Martin; Müller, Oliver; Vollmer, Robert; Becker, Jörg (Proceedings of the ACM Symposium on Applied Computing)

SME International Mode Choice Over Time: Forging a Link Between the Uppsala Model and Transaction Cost Economics - Maekelburger, B; Schwens, C; Kabst, Rüdiger (Entrepreneurship in the Global Firm (Progress In International Business Research, Volume 6))

SME performance in transition economies: The financial regulation and firm level corruption nexus - Gries, Thomas; Wieneke, Axel (Journal of Comparative Economics)

Studierendenorientierung: Wege und Irrwege eines Begriffs mit vielen Facetten - Reinmann, Gabi; Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Studierendenorientierung ist derzeit eines der Leitkonzepte für die Gestaltung der Lehre an Hochschulen. Ein kritischer Blick offenbart jedoch, dass der Begriff uneinheitlich und mit teils widersprüchlichen Konnotationen gebraucht wird. Der Beitrag analysiert die Begriffsverwendungen innerhalb verschiedener Hochschulkontexte. Dabei werden Widersprüche zwischen den vorgefundenen Konnotationen - insbesondere zwischen den Perspektiven des Hochschulmanagements und der Didaktik - identifiziert. Davon ausgehend wird mit dem Konzept der Bildungsorientierung eine Alternative vorgeschlagen, die auf das Kernziel der Hochschule als Bildungsorganisation verweist und die skizzierten Unschärfen vermeidet.
Keywords: Studierendenorientierung; Hochschulmanagement; Hochschuldidaktik

Sunk Cost Effect: The Impact of Delegating Decision Making to IT - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (INFORMS 2011 Annual Meeting, Track Digital Channel and It Usage)

Sunk Cost Effect: The Impact of Delegating Decision Making to IT - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (7th Symposium on Statistical Challenges in Electronic Commerce Research)

The Impact of Delegating Decision Making to IT on the Sunk Cost Effect - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (12th Workshop on Information Systems and Economics (WISE))

The Impact of Delegating Decision Making to IT on the Sunk Cost Effect - Herrmann, Philipp; Kundisch, Dennis; Rahman, M. (12th Workshop on Information Systems and Economics (WISE))

The Impact of Differential Capital Income Taxation on the Value of Risky Projects - Niemann, Rainer; Sureth-Sloane, Caren (Economics Bulletin)

The Impact of Interaction Effects Among Software Development Projects on Global Sourcing Decisions - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (5th Global Sourcing Workshop)

The influence of entrepreneurial traits on the strategic orientation and new product success in high-technology firms - Maekelburger, B; Zapkau, F B; Kabst, Rüdiger

The Mixed Accounting Model Under IAS 39: Current Impact on Bank Balance Sheets and Future Developments - Ebert, Michael; Bischof, Jannis (The Capco Institute Journal of Financial Transformation)

The Morphology of Service Bundling Settings - Beverungen, Daniel; Kohlborn, Thomas; Fielt, Erwin (22nd Australasian Conference on Information Systems (ACIS))

The Nexus between Monetary Policy, Banking Market Structure and Bank Risk Taking - Michalak, Tobias C.; Uhde, André
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.
Keywords: risk-taking channel; competition; concentration; bank soundness; European banking

The nexus between monetary policy, banking market structures and bank risk-taking - Uhde, André; Michalak, Tobias
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.

Three Approaches to Estimate Latent Interaction Effects: Intention and Perceived Behavioral Control in the Theory of Planned Behavior. - Steinmetz, Holger; Davidov, E; Schmidt, P (Methodological Innovation)

Time extension of sales promotions – How do customers react? - Münkhoff, E; Garnefeld, I; Bruns, A (Proceedings of the 40th European Marketing Academy (EMAC) Conference)

Time extension of sales promotions – How do customers react? - Münkhoff, Eva; Garnefeld, I.; Bruns, A. (40th EMAC Annual Conference, Ljubljana)

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Proceedings of the 30th International Conference on Lexis and Grammar 2011)

Towards Multilingual Biographical Event Extraction - Geierhos, Michaela; Bouraoui, Jean-Leon; Watrin, Patrick (Arbeiten zur Mehrsprachigkeit / Folge B)

Trade Openness and Economic Growth: A Panel Causality Analysis - Gries, Thomas; Redlin, Margarete

Unternehmensbewertung in Deutschland: Verfahren, Finanzplanung und Kapitalkostenermittlung - Homburg, Carsten; Lorenz, Michael; Sievers, Sönke (Controlling & Management)

Unternehmensbewertung in Deutschland: Verfahren, Finanzplanung und Kapitalkostenermittlung - Sievers, Sönke; Homburg, Carsten; Lorenz, Michael (Controlling & Management Review (VHB-JOURQUAL 3 Ranking D))

Verrechnungspreise in Speditionskooperationen - Opitz, Oliver (Ausgewählte Probleme des Logistikmanagements)

Verrechnungspreise in Speditionskooperationen - Faupel, Christian (Ausgewählte Probleme des Logistikmanagements)

Walk your talk: an experimental investigation of the relationship between word of mouth and communicators’ loyalty - Garnefeld, Ina; Helm, Sabrina; Eggert, Andreas (Journal of Service Research)

Weblogs zur Unterstützung der Theorie-Praxis-Integration in der Wirtschaftslehrenden-Ausbildung - Jenert, Tobias; Gebhardt, Anja; Käser, Reto (Zeitschrift für E-Learning)
Eine zentrale Herausforderung in der Ausbildung angehender Wirtschaftslehrpersonen stellt die sinnvolle Verknüpfung von Theorie- und Praxiserfahrungen dar. Im Rahmen der Ausbildung angehender Wirtschaftslehrpersonen an der Universität St. Gallen wird eine Lernumgebung gestaltet, die eine Verschränkung von Theorie- und Praxiserfahrungen ermöglichen soll. Die Lernprozesse der Studierenden werden dabei durch didaktisch angeleitete Weblogarbeit unterstützt. Trotz der Lernchancen, die sich aus einer Verknüpfung von theoretischen und praktischen Lernphasen ergeben, schätzen die Studierenden den Nutzen der Weblogarbeit als äusserst gering ein. Die Studierenden bei der reflexiven Integration praxisnaher und theoretischer Lernerfahrungen zu unterstützen, ist eine Herausforderung, die dezidierter Anleitung und Förderung durch die Lehrpersonen bedarf
Keywords: Weblog; Blog; e-learning; TEL; higher education; business education

What determines influenza vaccination take-up of elderly Europeans? - Schmitz, Hendrik; Wübker, Ansgar (Health Economics)

When the early bird catches the worm: The impact of training in retail - Hinerasky, Christiane; Fahr, Rene

Where are the participants? Including motivational aspects into theorizing and design in IS Research - Beverungen, Daniel; Wittchen, Marion; Becker, Jörg (Proceedings of the 19th European Conference on Information Systems)

Who follows the crowd—Groups or individuals? - Fahr, René; Irlenbusch, Bernd (Journal of Economic Behavior & Organization)

Why are the unemployed in worse health? The causal effect of unemployment on health - Schmitz, Hendrik (Labour Economics)

Workshop 16 Individuelle Förderung. Konzepte und Erfahrungen zur Berufsorientierung im Übergang - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A. (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011)

Worst case analysis for deterministic online algorithm in capacitated lot-sizing problem - Kaganova, Ekaterina (AIP Conference Proceedings)

Zur Bewertung von Verlustgesellschaften nach den Änderungen des §8c KStG durch das Wachstumsbeschleunigungsgesetz - Diller, M.; Kundisch, Dennis; Späth, T. (CORPORATE FINANCE biz)

Zur Neuregulierung des Bankensektors nach der Finanzkrise: Bewertung der Reformvorhaben der EU aus ordnungspolitischer Sicht - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (Die aktuelle Finanzkrise: Bestandsaufnahme und Lehren für die Zukunft, Schriften zur Ordnungsfragen der Wirtschaft)
Im Zuge der in den USA durch die exzessive Vergabe von Subprime-Krediten und deren Verbriefung ausgelöste Finanzkrise und der daraus folgenden weltweiten Wirtschaftskrise hat sich gezeigt, dass das bisherige System der Regulierung bzw. Überwachung von Finanzinstitutionen nicht ausreichend ist. Sowohl in den USA als auch in der Europäischen Union wird deshalb intensiv über ein neues System zur Regulierung von Finanzinstituten nachgedacht. Es ist zwar offen-sichtlich, dass eine wesentliche Ursache der Finanzkrise in den USA die Ermunterung der Finanzinstitute durch den Staat zur Vergabe von Immobilienkrediten an nicht ausreichend solvente Konsumenten war. Die vorhandenen Regulierungsinstrumente konnten die Krise jedoch nicht verhindern bzw. ausreichen abmildern. Das vorliegende Papier setzt sich zum Ziel, die Vorschläge zur Reform der Bankenregulierung zu evaluieren und insbesondere auf ihre potenziellen Wirkungen im Hinblick auf den Wettbewerb im Bankensektor zu überprüfen. Im Zuge der Diskussion über mögliche Lösungen existieren verschiedenste Vorschläge, die von Änderungen in Rechnungslegungsvorschriften über die Neuordnung der nationalen bzw. internationalen Finanzaufsicht bis hin zu einer stärkeren Berücksichtigung systemischer Risiken gehen. Die Auswirkungen der Finanzkrise haben gezeigt, dass die Abkehr von herkömmlichen Rechnungslegungssystemen hin zu Regeln der internationalen Rechnungslegung unter dem Schlagwort „Fair Value Accounting“ durchaus Gefahren in sich bergen kann. Die Debatte dreht sich insbesondere um die Frage, ob die neuen Rechnungslegungsvorschriften maßgeblich dazu beitragen, das regulatorische Eigenkapital einer Bank in Boomphasen zu erhöhen und in konjunkturellen Schwächephasen dagegen zu senken. In der Literatur ist in Hinblick auf diese Frage bislang keine einhellige Auffassung zu identifizieren. Pellens et al. (2009) gelangen zu dem Ergebnis, dass bankenaufsichtsrechtliche Normen an das IFRS-Zahlenwerk gebunden sind und dies für regulatorische Entscheidungen als besonders kritisch zu sehen ist. Durch das Konzept des Fair-Value-Accounting wurde das regulatorische Eigenkapital im Zeitraum von 2003 bis 2007 systematisch erhöht, woraus ein gestiegener Kreditvergabespielraum resultierte. Demgegenüber kommen Laux und Leuz (2009) im Rahmen einer empirischen Studie anhand von Mikrodaten aus den USA zu dem Ergebnis, dass Fair-Value-Accounting nur zum geringen Teil zu den Problemen der US Banken beigetragen hat und es im Rahmen ihrer Studie keine Evidenz für wesentliche Effekte dieses Rechnungslegungsverfahrens auf die massiven Abschreibungen der US Banken gibt. Beide Studien betonen aber auch, dass weitere empirische Forschung notwendig ist, bevor diese Frage abschließend geklärt werden kann. Die Frage des adäquaten Rechnungslegungssystems zeigt, wie vielfältig die Ursachen der gegenwärtigen Finanzkrise sind und wie schwer tatsächliche kausale Effekte zu identifizieren sind. Im folgenden Abschnitt werden zunächst die ordnungspolitischen Rahmenbedingungen einer angemessenen Bankenregulierung dargestellt. Der dritte Abschnitt umfasst einen kurzen Überblick über den Verlauf der Finanzkrise. In Abschnitt 4 diskutieren wir die wesentlichen Vorschläge zur Optimierung der Regulierung von Finanzinstituten. Abschnitt 5 evaluiert diese Vorschläge auch aus einer wettbewerbsökonomischen Perspektive. Diese Perspektive ist aus unserer Sicht vor allen Dingen notwendig, weil eine großer Teil der Reformdebatte aus Sicht der Finanzmarktstabilität geführt wird und infolgedessen Wettbewerbseffekte vernachlässigt werden. Das Fazit in Abschnitt 6 fasst unsere Ergebnisse zusammen und gibt einen Ausblick auf weiteren Forschungsbedarf aus Sicht der Wettbewerbsökonomie.

Zusatzbeiträge erhöhen die Preistransparenz: mehr Versicherte wechseln die Krankenkasse - Schmitz, Hendrik; Eibich, P.; Ziebarth, N.R. (Wochenbericht)

Zwischenbilanz des Lernfeldkonzepts - erfolgreiche Neuorientierung oder Irrweg - Tramm, T.; Kremer, H.-Hugo (Übergänge in der Berufsbildung nachhaltig gestalten: Potentiale erkennen - Chancen nutzen)

{Decision Making in Adaptive Manufacturing Systems: Multi-Objective Scheduling and User Interface

§§ 20 bis 23 UmwStG: Die Einbringung von Unternehmensteilen in eine Kapitalgesellschaft - Ansatz von Buchwerten oder gemeinen Werten - Maßbaum, Alexandra; Sureth-Sloane, Caren (Steuer und Studium)

Grenzüberschreitende Verlustverrechnungssysteme in Europa – Vorbilder für eine Reform der deutschen Organschaft? - Sureth-Sloane, Caren; Mehrmann, Annika; Dahle, Claudia (Steuer und Wirtschaft)

,,Blended Professionals´´ als Akteure einer institutionsweiten Hochschulentwicklung - Jenert, Tobias; Brahm, Taiga (Zeitschrift für Hochschulentwicklung)
Die aktuelle hochschuldidaktische Diskussion ist durch Schlüsselbegriffe wie Outcome- und Kompetenzorientierung geprägt. Allerdings sind die Strategien zur nachhaltigen Gestaltung der Lehr- und Lernpraxis bisher nur wenig differenziert. Der Beitrag stellt das Konzept einer "institutionsweiten Hochschulentwicklung" vor. Dieses spricht individuelles Handeln von Lehrenden und Lernenden sowie curriculare und organisationale Aspekte an. Mittels Experteninterviews wird gezeigt, dass Hochschulentwicklung eine "Third-Space-Funktion" zwischen Akademie und Administration einnimmt. Das personelle Profil solcher Einrichtungen verlangt nach "Blended Professionals", die sowohl als Servicepersonal als auch als Mitglieder der akademischen Welt wirkungsvoll agieren können.
Keywords: Hochschulentwicklung; educational development; higher education; Hochschuldidaktik

A Conceptual Framework for the International Staffing of Early Internationalizers - Isidor, R; Schwens, C; Kabst, Rüdiger (Internationale Unternehmungen und das Management ausländischer Tochtergesellschaften)

A decision-theoretic foundation of IS business value research - Schryen, Guido; Bodenstein, Christian (Proceedings of the 18th European Conference on Information Systems (ECIS 2010))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. Three research tasks are essential requisites on the path towards addressing this criticism: the synthesis of knowledge, the identification of lack of knowledge, and the proposition of paths for closing knowledge gaps. This paper considers each of these tasks by a) synthesizing key research findings based on a comprehensive literature review, b) identifying and unfolding key limitations of current research, and c) applying a decision-theoretic perspective, which opens new horizons to IS business value research and shows paths for overcoming the limitations. The adoption of this perspective results in a decision-theoretic foundation of IS business value research and includes the proposition of a consistent terminology and a research model that frames further research.
Keywords: Decision theory; IT value; IS assessment; IS evaluation

A Fuzzy Model for IT Security Investments - Schryen, Guido (Sicherheit 2010 : Sicherheit, Schutz und Zuverlässigkeit ; Konferenzband der 5. Jahrestagung des Fachbereichs Sicherheit der Gesellschaft für Informatik e.V. (GI), 5. - 7. Oktober 2010 in Berlin)
This paper presents a fuzzy set based decision support model for taking uncertainty into account when making security investment decisions for distributed systems. The proposed model is complementary to robabilistic approaches and useful in situations where probabilistic information is either unavailable or not appropriate to reliably predict future conditions. We ?rst present the speci?cation of a formal security language that allows to specify under which conditions a distributed system is protected against security violations. We show that each term of the security language can be transformed into an equivalent propositional logic term. Then we use propositional logic terms to de?ne a fuzzy set based decision model. This optimization model incorporates uncertainty with regard to the impact of investments on the achieved security levels of components of the distributed system. The model also accounts for budget and security constraints, in order to be applicable in practice.

A Sequential Model for Global Spam-Classifying Processes - Burkart, W.; Etschberger, S.; Klein, C.; Kundisch, Dennis (Proceedings of the International Conference on Information Systems (ICIS))

A User-Driven SOA for Financial Market Data Analysis - Guabtni, A.; Kundisch, Dennis; Rabhi, Fethi (Enterprise Modelling and Information Systems Architectures)

An Analysis of Literature Reviews on IS Business Value: How Deficiencies in Methodology and Theory Use Resulted in Limited Effectiveness - Schryen, Guido (Proceedings of the First Scandinavian Conference on Information Systems (SCIS))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. This paper assumes that literature reviews, which represent a powerful instrument for the identification and synthesis of knowledge, have not tapped their full potential to address this issue due to deficiencies in methodology. The analysis of 18 literature reviews published in pertinent academic outlets during the past 20 years shows such deficiencies. Two of the most critical weaknesses identified are (1) the lack of theory use in most reviews and (2) a weak linkage of reviews, resulting in little progress in theory and framework development. The systematic identification of these weaknesses and the extraction of promising methodological examples from past literature are the main contributions of this work, which supports the composition of more effective literature reviews in future research.
Keywords: Literature review; Business value; Information systems; Methodology; Theory

An empirical examination of the contribution of capabilities to the competitiveness of logistics service providers - Liu, Xiaohong; Grant, David B.; McKinnon, Alan C.; Feng, Yuanhua (International Journal of Physical Distribution & Logistics Management)

An ontology-based natural language service discovery engine--design and experimental evaluation - Becker, Jörg; Müller, Oliver; Woditsch, Manuel (European Conference on Information Systems)

Analyzing the Dynamics of Community Formation Using Brokering Activities - Trier, Matthias; Bobrik, Annette (Communities and Technologies 2007)

Applying heuristic methods for job scheduling in storage markets - Finkbeiner, Josef; Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (18th European Conference on Information Systems (ECIS 2010))
In double-sided markets for computing resources an optimal allocation schedule among job offers and requests subject to relevant capacity constraints can be determined. With increasing storage demands and emerging storage services the question how to schedule storage jobs becomes more and more interesting. Since such scheduling problems are often in the class NP-complete an exact computation is not feasible in practice. On the other hand an approximation to the optimal solution can easily be found by means of using heuristics. The problem with this attempt is that the suggested solution may not be exactly optimal and is thus less satisfying. Considering the two above mentioned solution approaches one can clearly find a trade-off between the optimality of the solution and the efficiency to get to a solution at all. This work proposes to apply and combine heuristics in optimization to gain from both of their benefits while reducing the problematic aspects. Following this method it is assumed to get closer to the optimal solution in a shorter time compared to a full optimization.
Keywords: Decision Support System; Algorithms; Optimization; Market Engineering

Are networks always beneficial? An empirical analysis on the relationship between knowledge intensity and international new venturing - Baum, M; Schwens, C; Kabst, Rüdiger

Assumptions in Service Research --- A Multi-Theoretical Perspective on the Development of Standards for the Integration of Goods and Services - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Nüttgens, Markus (XX. International RESER Conference)

Berufliches Lernen mit Web 2.0 - Medienkompetenz und berufliche Handlungskompetenz im Duell? - Pferdt, F. G.; Kremer, H.-Hugo (Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0)

Berufsorientierung als Herausforderung und Chance für die schulisch strukturierten Bildungsgänge des Übergangssystems - Kremer, H.-Hugo (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Besteuerung multinationaler Unternehmen in der EU – eine vergleichende Analyse ausgewählter Reformvorschläge - Sureth-Sloane, Caren; Bäumer, Michaela (Zeitschrift für Betriebswirtschaft)

Beteiligungsveräußerungen und Abgeltungssteuer - Sureth-Sloane, Caren (Besteuerung, Rechnungslegung und Prüfung der Unternehmen)

Bildung in Zeiten neuer Medien aus berufs- und wirtschaftspädagogischer Perspektive - Kremer, H.-Hugo (Bildung und Unterricht in Zeiten von Google und Wikipedia)

Capitalized investments with entry and exit options and paradoxical tax effects - Schneider, Georg; Sureth-Sloane, Caren (Review of Managerial Science)

Corporate Reputation and Customers’ Value Perceptions: A Dynamic Analysis - Frick, B; Eggert, A; Hogreve, J (Proceedings of the 39th EMAC Conference)

Creating and appropriating value in collaborative relationships - Wagner, Stephan M; Eggert, Andreas; Lindemann, Eckhard (Journal of business research)

Cultural Explorations: How Socio-material Contexts Influence Knowledge Interaction - Jenert, Tobias (Beyond Knowledge Management)

Customer Portfolio Management in E-Commerce - An Analytical Model for Optimization - Sackmann, S.; Kundisch, Dennis; Ruch, M. (Management Research Review)

Der Einfluss des Geschlechts auf die Gründungsintention – Ein meta-analytisches Pfadmodell (The influence of gender on entrepreneurial intention – a meta-analytical path model) - Haus, I; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger

Der Einfluss von Sozialkapital in der Asset Allocation von Privatanlegern - Kundisch, Dennis; Zorzi, R. (Journal of Banking and Financial Research)

Der Einfluss von Thin Capitalization Rules auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra

Die Wirkung ausländischer Direktinvestitionen auf die Beschäftigung im Heimatmarkt: Eine empirische Analyse des deutschen Mittelstands. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Different types of international new ventures: A latent class analysis - Baum, M; Schwens, C; Kabst, Rüdiger

Disentangling the Revenue and Cost Implications of the Service Transition: A Latent Growth Analysis - Eggert, A; Hogreve, J; Ulaga, W; Münkhoff, E (Proceedings of the 2nd ISBM Workshop at Harvard Business School)

Disentangling the revenue and cost implications of the service transition: A latent growth analysis - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (ISBM 2010 Academic Conference, Boston, MA)

Do Referral Reward Programs Enhance Customer Loyalty? – Results of a Propensity Score Matching Study - Garnefeld, I; Helm, S; Eggert, A; Tax, S (Proceedings of the 2010 AMA Summer Marketing Educators' Conference)

Does Customer Acquisition Jeopardize Customer Retention? - An Experimental Investigation in an Electronic Retailing Setting - Garnefeld, I; Woisetschläger, D; Eggert, A (Proceedings of the 18th International Colloquium in Relationship Marketing)

E-Services im Handel --- Auffindung und Dokumentation von Potenzialen zur Digitalisierung von Dienstleistungen für Hersteller und Kunden - Beverungen, Daniel; Knackstedt, Ralf; Winkelmann, Axel (Vertriebsinformationssysteme --- Standardisierung, Individualisierung, Hybridisierung und Internetisierung)

Educational change and innovative teaching practice: a study of the impact of reforms on the work of lectures in vocational education and training in England and Germany - Ertl, H.; Kremer, H.-Hugo (Orbis Scholae, Educational Change in the global context)

Effizienz Deutscher Krankenhäuser im Zeitablauf - Schmitz, Hendrik; Augurzky, B.

Einfluss der Finanzierung auf die Steuerbarkeit und Vorteilhaftigkeit von Investitionen - Kundisch, Dennis; Satzger, G. (Der Betrieb)

Einheitlicher europäischer Bankenmarkt? Eine Einschätzung der Wettbewerbssituation vor und nach der Finanzkrise - Paul, Stephan; Uhde, André (Wirtschaftsdienst)
Die schwerste Finanz- und Wirtschaftskrise nach dem Zweiten Weltkrieg befindet sich nun schon in ihrem dritten Jahr und wird in weiten Teilen der Öffentlichkeit als Paradebeispiel für ein gravierendes Marktversagen eingestuft. Dies hat über die unmittelbaren staatlichen Rettungsmaßnahmen hinaus den Ruf nach "Mehr Staat in der Kreditwirtschaft!" verstärkt und vielfältige Vorschläge zur Ausweitung und Verschärfung der Beaufsichtigung der Banken hervorgerufen (zuletzt im September 2009 beim Finanzgipfel in Pittsburgh). Noch lässt sich nicht präzise genug abschätzen, welche staatlichen Hilfen für die Kreditwirtschaft erforderlich sein werden und welche Veränderungen in der Bankenregulierung noch vorgenommen werden müssen. Dennoch wird in diesem Beitrag der Versuch einer Skizze möglicher Auswirkungen auf die Wettbewerbssituation des europäischen und deutschen Bankenmarktes speziell im Retail-Segment unternommen. Um die durch die Finanzkrise hervorgerufenen Veränderungen einschätzen zu können, ist jedoch zunächst ein kurzer Blick auf die wichtigsten Etappen und Ergebnisse der europäischen Finanzmarktintegration erforderlich.
Keywords: Finanz- und Wirtschaftskrise; Bankenmarkt

Empirische Analyse der Unternehmensbewertung für die Erbschaftsteuer mit dem vereinfachten Ertragswertverfahren - Müller, Jens; Sureth-Sloane, Caren

Enabling Individualized Recommendations and Dynamic Pricing of Value-Added Services through Willingness-to-Pay Data - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Frohs, Margarethe; Müller, Oliver; Weddeling, Matthias; Knackstedt, Ralf; Steiner, Michael (Electronic Markets)

Enlarging the focus on the role of competencies, abilities, and personality in management research. - Kabst, Rüdiger; Isidor, R; Steinmetz, Holger; Schwens, C (Management Revue: The International Review of Management Studies.)

Enlarging the Focus on the Role of Competencies, Abilities, and Personality in Management Research. - Steinmetz, Holger; Schwens, C; Isidor, R; Kabst, Rüdiger (Management Revue: The International Review of Management Studies.)

Entrepreneurship and Structural Economic Transformation - Gries, Thomas; Naudé, Wim (Small Business Economics)

Explaining the Trading Venue Decision of Private Online Investors - An Empirical Study - Herrmann, Philipp; Kundisch, Dennis (International Workshop on Enterprise Applications, Markets and Services in the Finance Industry (FinanceCom))

Explanatory factors for firms’ use of temporary agency work in Germany - Thommes, Kirsten; Weiland, Katrin (European Management Journal)

Exploring the Effects of Referral Reward Programs on Satisfied and Dissatisfied Customers - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 2010 AMA Winter Marketing Educators' Conference)

Exploring the effects of referral reward programs on satisfied and dissatisfied customers - Garnefeld, I.; Münkhoff, Eva; Hogreve, J.; Eggert, A. (2010 AMA Winter Academic Conference, New Orleans, LA)

Fostering the Virtualization of Service Processes and Touch Points --- Identification and Documentation of E-Service Potential in Retail Networks - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Winkelmann, Axel (Lecture Notes in Informatics)

From "Take-it-or-leave-it" offers to "Take-it-or-be-left-out" Ultimatum - A trade mechanism for Online Services - Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (18th European Conference on Information Systems (ECIS 2010))
In a world, where more and more businesses seem to trade in an online market, the supply of online services to supply the ever-growing demand could quickly reach its capacity limits. Online service providers may find themselves maxed out at peak operation levels during high-traffic timeslots but too little demand during low-traffic timeslots, although the latter is becoming less frequent. At this point not only deciding which user is allocated what level of service becomes essential, but also the magnitude of the service provided, can be controlled by pricing. Pricing is an important factor when efficient and acceptable allocation of resources between individuals must be reached. Without prices, transferring or sharing goods would be impossible. In sharing information, pricing a product however is not as simple as relatively pricing an apple or a pear. Often the costs, and hence the prices are simply unknown. Backed by this scenario, the online services market could be combined with the market design mechanism of diamonds. For this we propose an ultimatum pricing strategy which effectively allows for valuations to be accounted for, but no longer a necessity when pricing in grid, cloud or other online computing environments.
Keywords: Posted Price; Ultimatum Game; Energy Efficiency; Mechanism Design

Geschäftsmodelle in virtuellen Spielwelten

Growth and Internationalization of Renewable Energy and New Technology-Based Firms - Schwens, C; Steinmetz, Holger; Kabst, Rüdiger (Innovation and International Corporate Growth)

Handels- und steuerrechtliche Kapitalkontenfortschreibung und deren Einfluss auf die Verlustverrechnung bei Personengesellschaften - Kopplin, Anja; Maßbaum, Alexandra; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)